NEW SCHEME OF MIGNOTTE (t,n) COLLABORATIVE SECRET SHARING ON CLOUD STORAGE - Ekaputri, Dhea; Guritman, Sugi; Jaharuddin, Jaharuddin (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2025)
Cloud storage is an internet-based data storage service that allows users to collaborate to store, manage, and access data remotely. However, this collaborative characteristic creates challenges in security and privacy. One potential solution to these issues is implementing a collaborative secret sharing scheme. This research proposes a modified Mignotte collaborative secret sharing scheme by introducing a detector parameter to detect cheating. Additionally, the scheme is designed so that participants with multiple privileges only need to store a single share. The main contribution of this research is the integration of a cheating detection mechanism into the Mignotte collaborative secret sharing scheme while maintaining storage efficiency. Experimental results show that the scheme produces correct outputs across various test cases. The proposed modification enhances the security of the secret sharing scheme for cloud storage applications by protecting against cheating and unauthorized access. However, the current scheme is limited to detection without identifying the cheater. Future research can focus on developing mechanisms for further identifying cheaters to enhance overall security.